Cracks in the foundations of growth: What will the housing debacle mean for the US economy? - Dimitri B. Papadimitriou; Greg Hannsgen; Gennaro Zezza (Levy Economics Institute of Bard College, 2007)
With economic growth having cooled to less than 1 percent in the first quarter of 2007, the economy can ill afford a slump in consumption by the American household. But it now appears that the household sector could finally give in to the pressures of rising gasoline prices, a weakening home market, and a large debt burden. The signals are still mixed; for example, while April's retail sales numbers caused concern, May's were much improved, and so was the ISM manufacturing index for June. Consumption growth indicates a slowdown. This Public Policy Brief examines the American household and its economic fortunes, concentrating on how falling home prices might hamper economic growth, generate social dislocations, and possibly lead to a full-blown financial crisis.
Keywords: 330; Wohnungsmarkt; Branchenkrise; Hypothek; Bankenkrise; Wirtschaftswachstum; USA